Rubber legs and white tail-hairs - McManus, Patrick F. frey50 (New York Holt, 1988)
Offers a humorous collection of tales, including "Muldoon in Love," a story that features a teacher who wore the same suit to school for thirty years.
Muldoo in love - Cry wolf - Pigs - The MFFFF - Summer Reading - Angler's dictionary - The mountain - Not long for this whirl - claw of the Sea-Puss - A Really nice blizzard - Rubber legs and white tail-hairs - Nude, with other wildlife - the belcher - Shooter - The last flight of Homer Pidgin - A boy and his (Ugh!) dog - To filet or not the filet - What's in a name, Moonbeam? - Loud screeching and other tips on getting lost - the big fix - The fine art of delay - Gun-trading - Throwing stuff - Letter to Santa - The cabin at Spooky Lake - Outdoor burnout - Advanced duck-hunting techniques
"An Owl Book."
Keywords: American wit and humor